UPAYA MENINGKATKAN KEAKTIFAN BELAJAR MAHASISWA PENDIDIKAN MATEMATIKA DENGAN PENDEKATAN PROBLEM POSING - Fahmi, Syariful (Universitas Tanjungpura, 2017)
Problems in learning introductory computer science which need urgent solution is the problem related with the students learning actinevess. Along with the approach of problem posing, problem solving efforts above got the right momentum. Learning approach used in this research is problem posing approach. The purpose of the research is to increase students? learning activeness. This research activity involves two lecturers and 21 students in course of introduction of computer science at semester 4 academic year of 2015/2016. The data collected using the students activity sheet and analyzed in qualitative descriptive. Based on the results of data analysis it is known that the use of the problem posing approach can raise average students learning on the activeness of cycle 1 that included in the category of low and at cycle 2 is included in the category of middle. It means an increase in students? learning activeness after organized research activities. Keywords: learning activeness, students creativity, problem posing approach